An updated catalogue of the Histeridae (Insecta: Coleoptera) of the Arabian Peninsula, with biogeographical remarks - Penati, Fabio; Vienna, Pierpaolo (Zootaxa, 2006)
The histerid fauna of the Arabian Peninsula is evaluated. As a result of the study of specimens recently collected in Oman by the scientific expeditions of the Museum of Natural History and Territory of Calci (University of Pisa, Italy), and compiling new data from 15 public and private collections, and literature records, the total number of Histeridae known from the Arabian Peninsula now stands at 67 species, without taking into account dubious species and undetermined taxa (9).Of these 67 species, in total 18 are reported for the first time: 4 for the Arabian Peninsula [Teretrius (Neotepetrius) parasita Marseul, Saprinus (Saprinus) flexuosofasciatus Motschulsky, Chalcionellus hauseri (Schmidt), Hypocacculus (Nessus) hosseinius (Théry)], 9 for Oman [Pachylister luctuosus (Marseul), Hister castus Lewis, Atholus bimaculatus Linnaeus, Atholus scutellaris (Erichson), Saprinus (Saprinus) splendens (Paykull), Hypocacculus (Colpellus) praecox (Erichson), Hypocacculus (Hypocacculus) harmonicus (Marseul), Hypocacculus (Hypocacculus) metallescens (Erichson), Hypocaccus (Hypocaccus) fochi (Auzat)], 2 for Yemen [Saprinus (Saprinus) tenuistrius tenuistrius Marseul, Chalcionellus tunisius (Marseul)] and 3 for Kuwait [Saprinus (Saprinus) moyses Marseul, Pholioxenus mesopotamicus Olexa, Paravolvulus syphax (Reitter)].Histeridae are now known for four national states (Saudi Arabia, Yemen, Oman and Kuwait), while there are no records for Qatar or United Arab Emirates. An updated comprehensive catalogue of the histerid fauna of the Arabian Peninsula is provided.Analysis of faunal affinities shows that it mostly consists of Palearctic species (24 species, equal to 35.9%), followed by Afrotropical and Afrotropico-Mediterranean species (22 species, 32.8%), and cosmopolitan/subcosmopolitan species (7 species, 10.4%); endemics stand at 5 species (7.5%), while species of undefined chorology at 9 (13.4%). On the whole these numbers fit well the largely accepted biogeographical assumption that indicates the Arabian Peninsula as a transitional zone between the Regions Palearctic, Afrotropic and, to a lesser degree, Indo-Malay (e.g., Büttiker 1979). Moreover, a distinctive distributional pattern has been recognised: “Afrotropical” Histeridae are almost exclusively present in the southern and south-western parts of the peninsula, while “Palearctic” Histeridae are mostly present in the inner central and south-eastern parts of the peninsula.Finally, the synonymy Saprinus (Saprinus) osiris Marseul, 1862 = Saprinus (Saprinus) ornatus Erichson, 1834 stated by Müller (1933), but neglected by Mazur (1976, 1984, 1994, 1997), is considered valid.